High rejection reverse osmosis membrane for removal of N-nitrosamines and their precursors. (15th March 2018) - Fujioka, Takahiro; Ishida, Kenneth P.; Shintani, Takuji; Kodamatani, Hitoshi
Abstract: Direct potable reuse is becoming a feasible option to cope with water shortages. It requires more stringent water quality assurance than indirect potable reuse. Thus, the development of a high-rejection reverse osmosis (RO) membrane for the removal of one of the most challenging chemicals in potable reuse – N -nitrosodimethylamine (NDMA) – ensures further system confidence in reclaimed water quality. This study aimed to achieve over 90% removal of NDMA by modifying three commercial and one prototype RO membrane using heat treatment. Application of heat treatment to a prototype membrane resulted in a record high removal of 92% (1.1-log) of NDMA. Heat treatment reduced conductivity rejection and permeability, while secondary amines, selected as N -nitrosamine precursors, were still well rejected (>98%) regardless of RO membrane type. This study also demonstrated the highly stable separation performance of the heat-treated prototype membrane under conditions of varying feed temperature and permeate flux. Fouling propensity of the prototype membrane was lower than a commercial RO membrane. This study identified a need to develop highly selective RO membranes with high permeability to ensure the feasibility of using these membranes at full scale. Graphical abstract: Highlights: Heat-treated prototype RO membrane achieved a 92% removal of NDMA. Rejection by the RO membrane remained stable under variable temperature and flux. Rejection of DMA, an NDMA precursor, by the high rejection RO membrane was 99%. However, permeability was considerably reduced by heat treatment.